Technical notes on the placement of cerebral microdialysis: A single center experience - Falcone, Joseph A.; Chen, Jefferson W. (Frontiers in Neurology, 2023)
BACKGROUND: Cerebral microdialysis enables monitoring of brain metabolism and can be an important part of multimodal monitoring strategies in a variety of brain injuries. Microdialysis catheters can be placed in brain parenchyma through a burr hole, a cranial bolt, or directly at the time of an open craniotomy or craniectomy. The location of catheters in relation to brain pathology is important to the interpretation of data and guidance of interventions. METHODS: Here we retrospectively review the use of cerebral microdialysis at a US Regional Medical Center between March 2018 and February 2022 and provide detailed descriptions and technical nuances of the different methods to place microdialysis catheters. RESULTS: 82 unique microdialysis catheters were utilized in 52 patients. 35 (42.68%) were placed via a quad-lumen bolt and 47 (57.32%) were placed through craniotomies. 27 catheters (32.93%) were placed in a perilesional location, 50 (60.98%) were located in healthy tissue, and 6 (7.32%) were mispositioned. No significant difference was seen between placement by bolt or craniotomy in regard to perilesional location, mispositioning, or complications. CONCLUSION: With careful planning and thoughtful execution, cerebral microdialysis catheters can be successfully placed though a variety of strategies to optimize and individualize brain monitoring in different clinical settings. This paper provides a detailed guide for the various methods of catheter placement to help providers begin or expand their use of cerebral microdialysis.